Impact of Sleeve Gastrectomy on Weight Loss, Glucose Homeostasis, and Comorbidities in Severely Obese Type 2 Diabetic Subjects. (20th February 2011) - Nosso, G.; Angrisani, L.; Saldalamacchia, G.; Cutolo, P. P.; Cotugno, M.; Lupoli, R.; Vitolo, G.; Capaldo, B.
Abstract : This study was undertaken to assess medium-term effects of laparoscopic sleeve gastrectomy (LSG) on body weight and glucose homeostasis in severely obese type 2 diabetic (T2DM) subjects. Twenty-five obese T2DM subjects (10 M/15 F, age45 ± 9 years, BMI48 ± 8 kg/m 2, M ± SD) underwent evaluation of anthropometric/clinical parameters and glucose homeostasis before, 3 and 9–15 months after LSG. Mean BMI decreased from48 ± 8 kg/m 2 to40 ± 9 kg/m 2 (P < .001 ) at 3 months and34 ± 6 kg/m 2 (P < .001 ) at 9–15 months after surgery. Remission of T2DM (fasting plasma glucose < 126 mg/dL andHbA1c < 6.5 % in the absence of hypoglycemic treatment) occurred in all patients but one. There was a remarkable reduction in the percentage of patients requiring antihypertensive and hypolipidemic drugs. Our study shows that LSG is effective in producing a significant and sustained weight loss and improving glucose homeostasis in severely obese T2DM patients.